Substantiating the roles of higher education system in Malaysia: identifying issues and charting the way forward - Abdul Rahman, Shukran; Khalid, Haniza; Mohd Yusof, Danial (Centre for Political, Economic and Social Research, 2017)
Education is one of the key factors for national transformation. Higher education (HE) stands as an important sector in any country including Malaysia, which roles range from workforce supplier to knowledge and innovation centers. During the early days of higher education focus has been given to producing knowledgeable workforce. Over time, the roles have changed to producing new knowledge and solving problems faced by the societies. The changes perpetuate, driven by various factors, especially the direction of the country which strategies have made impacts on the ways universities behave or operate. In Malaysia, the National Higher Education Strategic Plan (NHESP), was launched in August 2007 to drive transformation of HE with the main agenda of producing graduates who are knowledgeable and competent in their fields, innovative, multilingual and technology-savvy. Nevertheless we argue that the roles of higher education are more than just producing workforce, in that HEs must help the country shape the advancement of social growth and economic prosperity. Thus this paper addresses several pertinent gaps between the current Malaysian HE landscape and various future global scenario. Consequently, we need to assess whether the conception of NHESP has recognized this gap and considered measures to address it for the benefit of the direct stakeholders and the country as a whole. The findings will enlighten the HE authority of the timely issues that require proper attention, and in turn steer the direction of HE services.